Tracheostomy before and during COVID-19 pandemic - Jensterle, Sara (Radiology and oncology (Ljubljana), 2024)
Background: The aim of the study was to provide insight into the influence of the COVID-19 on the frequency and characteristics of urgent and emergent tracheostomies (TS), comparing data collected both before and during the pandemic. Our two hypotheses were that during COVID-19, more TS were performed in the emergent setting and that during COVID-19 more TS were performed under general anaesthesia. Patients and methods: The research was retrospective. The study period included the two years before and after the COVID-19 outbreak in Slovenia. Forty-one patients in each period met the inclusion criteria. Their medical charts were reviewed. The anamnestic, clinical, surgical and anaesthesiological data were collected. The two groups of patients from corresponding time periods were statistically compared. Results: Predominantly men required the surgical resolution of acute upper airway obstruction (76% of patients). The causes for acute respiratory distress included head and neck cancer (62%), infections (20%), vocal cord paralysis (16%), and stenosis (2%). There were no statistically significant differences either in the (emergent/urgent) setting of TS or in the type of anaesthesia used. Both hypotheses were rejected. A statistically significant rise in use of the C-MAC laryngoscope during COVID-19 (from 3% to 15%) was reported. Conclusions: The outbreak of COVID-19 did not have a statistically significant effect on the frequency of performing emergent and urgent tracheostomies nor on the use of general or local anaesthesia. It did, however, require a change of intubation technique. Consequently, a significant rise in the use of the C-MAC laryngoscope was noted.
Keywords: anestezija; obstrukcija zgornjih dihalnih poti; orotrahealna intubacija; SARS-CoV-19; traheostomija